2008
DOI: 10.1038/cdd.2008.69
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 represses ‘stemness’ by repressing ΔNp63

Abstract: The epidermis, the outer layer of the skin composed of keratinocytes, is a stratified epithelium that functions as a barrier to protect the organism from dehydration and external insults. The epidermis develops depending on the transcription factor p63, a member of the p53 family of transcription factors. p63 is strongly expressed in the innermost basal layer where epithelial cells with high clonogenic and proliferative capacity reside. Deletion of p63 in mice results in a dramatic loss of all keratinocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
357
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(380 citation statements)
references
References 40 publications
19
357
1
3
Order By: Relevance
“…1243 RESEARCH ARTICLE miR302/367 and lung endoderm development Little is known about the ability of miRNAs to regulate tissuespecific progenitor populations. In the skin, miR203 promotes differentiation of skin basal progenitor cells by repressing the important skin progenitor maintenance factor p63 (Lena et al, 2008;Yi et al, 2008;Wei et al, 2010). However, less is known in the lung.…”
Section: Research Articlementioning
confidence: 99%
“…1243 RESEARCH ARTICLE miR302/367 and lung endoderm development Little is known about the ability of miRNAs to regulate tissuespecific progenitor populations. In the skin, miR203 promotes differentiation of skin basal progenitor cells by repressing the important skin progenitor maintenance factor p63 (Lena et al, 2008;Yi et al, 2008;Wei et al, 2010). However, less is known in the lung.…”
Section: Research Articlementioning
confidence: 99%
“…[16][17][18][19] Certain miRNAs were shown to mediate the induction of cell death, cell cycle arrest, and senescence and contribute to epithelial stem cell maturation. [18][19][20] We previously observed that the head and neck squamous cell carcinoma (HNSCC) cells exposed to CIS displayed a dramatic downregulation of DNp63a through an ATMdependent phosphorylation mechanism. 21,22 We also showed that phospho (p)-DNp63a is critical for the transcriptional regulation of downstream mRNAs in HNSCC cells.…”
mentioning
confidence: 99%
“…PCR primers used to obtain them are available on request. Luciferase assays were performed as described in Lena et al (16). Cells were transfected with 100 ng of pGL3 vectors, 12 pmol of pre-miRNA or a scrambled sequence (Ambion), and 10 ng of Renilla luciferase pRL-CMV vector (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…p63 KO mice completely lack skin and skin derivatives and die within a few hours after birth due to dehydration (13,14). The most abundant p63 isoform in the epidermis is ΔNp63, which is highly expressed only in the basal compartment of proliferating keratinocytes (13), and its expression is tightly regulated by miR-203 during keratinocyte differentiation (15,16). Studies have shown that p63 is involved in senescence pathways, as its absence in conditional knockout mice induces premature aging (17)(18)(19).…”
mentioning
confidence: 99%